Gincana lúdica com elementos da comunicação não violenta na educação física escolar: aprendizagens decorrentes - Trovo, Cássia de Souza (Universidade Federal de São Carlos, 2025)
Indiscipline and aggression have negatively impacted the school environment, also affecting the Physical Education curriculum. This study aimed to describe and analyze the development of a didactic unit on Games and Play in Physical Education classes, organized as a playful activity in the form of a challenge, integrated with elements of Nonviolent Communication (NVC). The research, which adopted a qualitative approach, involved a pedagogical intervention with a 4th-grade class in a public school within the municipal system of Ribeirão Preto-SP, with the participation of 25 students in 10 lessons, each lasting 50 minutes. Data were collected through Field Notes, which were then analyzed using coding categories. The identified categories were: A) Challenges: Issues such as the presence of students from other classes in the gymnasium and resistance to NVC hindered the development of a collaborative environment, highlighting the need for ongoing strategies to support lesson development and the achievement of educational goals; B) Advances: The playful activity in the form of a challenge fostered progress, including the development of active listening, collective problem-solving, and respect for individual limitations, thereby strengthening collaboration and trust. Emphasizing the process rather than the outcome contributed to the creation of a more inclusive environment. Indiscipline and aggression have negatively impacted the school environment, also affecting the Physical Education curriculum. This study aimed to explore how the development of a teaching unit on Games and Play, organized as a playful activity in the form of a challenge, integrated with the principles of Nonviolent Communication (NVC), could contribute to a more collaborative and respectful school environment. The research, which adopted a qualitative approach, involved a pedagogical intervention with a 4th-grade class in a public school within the municipal system of Ribeirão Preto-SP, with the participation of 25 students in 10 lessons, each lasting 50 minutes. Data were collected through Field Notes, which were then analyzed using coding categories. The identified categories were: A) Challenges: Issues such as the presence of students from other classes in the gymnasium and resistance to NVC hindered the development of a collaborative environment, highlighting the need for ongoing strategies to support lesson development and the achievement of educational goals; B) Advances: The playful activity in the form of a challenge fostered progress, including the development of active listening, collective problem-solving, and respect for individual limitations, thereby strengthening collaboration and trust. Emphasizing the process rather than the outcome contributed to the creation of a more inclusive environment. Despite the challenges encountered, organizing the playful activity from a perspective that values relationships over competitiveness proved to be a promising path for transforming interpersonal relationships and fostering a more harmonious and welcoming school environment.
Playful challenge with elements of nonviolent communication in school physical education: learning outcomes
Keywords: Educação Física Escolar; Jogos e Brincadeiras; Comunicação Não Violenta; Gincana Lúdica; School Physical Education; Games and Play; Nonviolent Communication; Playful Challenge; CIENCIAS DA SAUDE::EDUCACAO FISICA